2005
DOI: 10.1515/crll.2005.2005.584.29
|View full text |Cite
|
Sign up to set email alerts
|

Exponential sums and congruences with factorials

Abstract: We estimate the number of solutions of certain diagonal congruences involving factorials. We use these results to bound exponential sums with products of two factorials n!m! and also derive asymptotic formulas for the number of solutions of various congruences with factorials. For example, we prove that the products of two factorials n!m! with maxfn; mg < p 1=2þe are uniformly distributed modulo p, and that any residue class modulo p is representable in the form m!n! þ n 1 ! þ Á Á Á þ n 47 ! with maxfm; n; n 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In the present paper we improve some of the results from [6] and [7]. In [6] it is shown that any residue class λ modulo p can be represented in the form…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…In the present paper we improve some of the results from [6] and [7]. In [6] it is shown that any residue class λ modulo p can be represented in the form…”
mentioning
confidence: 69%
“…Some progress in this direction has been made in [5,6]. In particular, multiplicative character sums and double exponential sums involving factorials have been estimated.…”
mentioning
confidence: 99%
“…and single multiplicative character sums as above with a = 0 are estimated in [68] and [69], respectively. and…”
Section: Combinatorial Sequencesmentioning
confidence: 99%
“…Here, we continue to study exponential sums and various congruences with factorials which have been considered in [l, 2,3,5,6,7,8] and use some results and methods of [2,3] to study the analogue of the Waring problem with factorials.…”
Section: Introductionmentioning
confidence: 99%